Occupational Analysis with DACUM: A Case Study - Tarkan Düzgünçınar; İlhan Günbayı (Anı Publishing, 2020)
In institutions with hierarchical structures, as in others, the knowledge and skills of the personnel must be in accordance with the requirements of the positions held. Knowledge and understanding by the HR recruiting officer, of the conditions of employment, qualifications required and of the tasks to be performed in a position, will facilitate the employment and appointment of personnel. The examination of a position is called Occupational Analysis and is an important part of human resources management, providing data on recruitment systems, training programs, performance management and compensation systems. The aim of this study is to apply the results of a DACUM (Develop A CUrriculuM) process, known as a Competency Based Business Analysis method, in order to develop job descriptions and to determine training needs and competencies required of employees. With this study, the knowledge, skills and behavior needs of the institution, along with trends for the future, will be determined.